Preliminary Study on Water Absorption and Swelling for Plain and Honeycomb Rubber Wood - Yuhazri, M.Y.; Jennise, T.T.T.; Kamarul, A.M.; Edeerozey, A.M.M.; Hussein, N.I.S. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Rubber wood receives good reviews such as minimal shrinkage and high durability. In composites, rubber wood is often used in the form of wood dust or flour as the filler, but has yet been employed as a honeycomb core in the sandwich composites. Since the rubber wood honeycomb composite is targeted to replace plywood in the furniture industries in Malaysia, a country with high humidity, it is important to investigate its water absorption and swelling condition. It is because the surface area will be highly increased when it is designed into the honeycomb. The plain and honeycomb rubber wood as well as plain plywood were immersed into the water for seven days. Their weight, volumes and density for before and after the immersion were compared and analysed. The honeycomb wood absorbed the highest percentage of water with the minimum volume change compared to the plain rubber wood and plywood. Due to the honeycomb design of the rubber wood, its density maintain as the lowest among the specimens.